Cinemotion, a Program of Cognitive Remediation to Improve the Recognition and Expression of Facial Emotions in Schizophrenia: A Pilot Study - Sevos, Jessica; Grosselin, Anne; Gauthier, Michael; Carmona, Florian; Gay, Aurélia; Massoubre, Catherine (Frontiers in Psychiatry, 2018)
Objective: Patients with schizophrenia exhibit impaired social cognition, especially in the recognition and expression of facial emotions, aspects of communication profoundly interlinked in an embodied approach of cognition. Nevertheless, many training programs have been developed that focus on either of these deficits but not both. We therefore designed a training program, Cinemotion, intended to remedy the 2 deficits and investigated its feasibility and effects in patients with schizophrenia. Design: Thirty-one patients undergoing treatment for schizophrenia and presenting deficit in emotion recognition were randomized to a group of 16 to undergo Cinemotion training, delivered in weekly group sessions, and to a control treatment group of 15. At the conclusion of training or after 10 weeks in controls, we reassessed and compared original and final results to determine improvement. Methods: Facial emotions recognition (TREF), empathy (Questionnaire of Cognitive and Affective Empathy, QCAE) and attributional style (Ambiguous Intentions Hostility Questionnaire, AIHQ) were assessed before (T0) and after (T1) the program. External evaluators also assessed ability and accuracy of Cinemotion participants to self-generate facial emotion expression in response to verbal instruction. Results: Between T0 and T1, Cinemotion participants significantly improved total TREF, sadness, disgust and anger scores, compared to findings in control treatment group. They also improved their ability and accuracy to self-generate facial expressions, especially sadness and fear, with no significant improvement in other components of social recognition. Conclusions: Our findings show the apparent efficacy of training using the Cinemotion program to improve the recognition and expression of facial emotions in schizophrenia.